Psychology of Leadership: Understanding AI Adoption, Self-Efficacy, Green Creativity, and Risk Perception among Oman’s Business Bosses - Fadi Abdelfattah; Mohamed Salah; Khalid Dahleez; Hussam Al Halbusi (Changing Societies & Personalities)
Artificial intelligence (AI) is at the forefront of transformative changes in organizational innovation. This study examines the social psychology underpinning AI adoption among Oman’s top business leaders, including CEOs, founders, and senior executives, to explore how green creativity, positive mental well-being, and risk perception converge with self-efficacy as a critical moderating force. Significant positive correlations were identified between most variables in the data set of 214 prominent Omani leaders using structural equation modeling and SmartPLS 4 software. The findings illustrated how Oman’s business leaders harnessed AI to align technological capabilities with deeply ingrained cultural values and communal aspirations. By situating these insights within Oman’s strategic vision of economic diversification and sustainability, this study underscored AI’s potential to catalyze organizational performance and environmentally conscious innovation. In addition, the moderating role of self-efficacy highlighted the importance of leadership confidence in navigating the complexities of AI integration. These discoveries have important implications for scholars, policymakers, and industry practitioners in Oman and other collectivist and emerging markets. By combining technology and human psychology, this study accentuates the need for thoughtful integration of AI, ensuring that rapid digital transformations remain culturally resonant, ethically grounded, and person-centered in an era of continuous change.